I πονηροί tra Aristofane e l’oratoria - Massimiliano Labanca (Annali Online dell'Università di Ferrara. Sezione Lettere)
The first aim of this paper is to illustrate the various meanings of the word πονηρός (together with the antonym χρηστός) and especially its usage from the last quarter of V century b.C. to the first half of IV, both in theatrical literature and in political jargon; the semantic gap between the etymological sense of this term and its occurrences in post-Periclean age is due to the great social renewals in VI-V cent. and next to the decline of the democratic parabola in Athens. Consequently, the paper shows the tight connections between comic and political lexicon: according to Alessandro Grilli, all Aristophanes’ comedies concern politics and therefore refer to its vocabulary in order to inspire audience’s laugh and blame.